Pelestarian Budaya Batik Tulis Melalui Penggalian Potensi Kriya Batik Pewarna Alami Bagi Penggerak Deswita Wonolopo - Imam Husni Al Amin; Edy Winarno; Dewi Handayani U. N.; Veronica Lusiana (Universitas Persada Indonesia YAI, 2023)
The Wonolopo tourist village was designated by the mayor of Semarang as one of theleading tourist villages in the city of Semarang, which is located in Mijen sub-district, WestSemarang, Central Java. Wonolopo tourist village has a lot of local potential with natural wealthand uniqueness that can be proud of as one of the cultural and educational tour packages fortourists. With the uniqueness of Kampoeng Jamunya which can be juxtaposed with theexploration of natural dyed batik, it becomes the main attraction to be presented for tourists whowant to see the uniqueness of the Wonolopo tourist village area.Most of those who are driving tourist villages and tourism awareness groups (pokdarwis)do not understand the process of writing batik, let alone the use of natural dyes that can beobtained from around. One of the efforts to optimize the existing potential needs to be carriedout on an ongoing basis, training and technical guidance mainly for the community that drivesthe Tourism village in the form of written batik / stamp using the natural dye Blue Indigo. The training was given in stages starting from handling the fabric with mordanting, blazing the motifonto a piece of white cloth, painting according to the pattern drawn, the next process dyeing thefabric with natural Indigo blue dye, and finally slapping it off to remove the wax from the stick.The last process, the cloth is rinsed until it is clean from the lime that is present with the Indigopaste